Ontologia do serviço de referência em unidades de documentação - Araújo, Irlana Mendes de (2021)
Reference services are characterized by a series of activities, whose main function is to provide direct assistance to the user. As the document explosion has grown and information has become considered as a major input for society, this service has improved to serve more and more in different formats, whether in the analog or digital environment. The reference, in turn, is pointed as the central core of the information units, and it is through it that the interface librarian-user of information takes place, being necessary to pay attention to the constitution of the services and products offered in the documentation units. In this perspective, and considering Ontologies as a new and exciting category of information and knowledge representation systems, their usefulness for this research is based on modeling the knowledge domain, in order to highlight the daily actions of the librarian and the terminologies used in the Reference Service. In this sense, this research has the general objective of building a Reference Service Ontology model, aiming at a better understanding of the components of this service and the quality of the service provided by the documentation units. This configures an applied research and is based on structuralism. As a methodological strategy, to determine the Ontology, the Methontology, elaborated by Fernandez; Gomez-Perez and Juristo, was taken as a basis. They structured this methodology, exposing the following stages: specification, conceptualization, knowledge acquisition, integration, implementation, evaluation and documentation. The ONTOSR was established in the Protégé software - Stanford University [Palo Alto-USA], observing the stages of Methontology. The results show the terminology occurring in the reference offers and the relationships among the terms, so that they mirror the essence of this service. In conclusion, it is observed that ONTOSR, by transposing the formal and consensual representation of domain knowledge, also favors exclusive access to the information and knowledge represented.